Evaluation of oral health literacy among medical interns in Saudi Arabia: A cross-sectional study - Ruba Alkadhi; Abdulsalam Thekkiniyakath Ali; Khulud Alotaibi; Raghad Alhassoun; Lujain AlNojaidi; Nada Alharbi; Nouf Almagati; Ghadah Aldakheel (Wolters Kluwer Medknow Publications, 2023)
Introduction: Physicians can play an essential role in promoting their patients' oral health by integrating oral health screening and education into their practices. Thus, physicians' oral health literacy (OHL) level can determine their role in oral health promotion. Aim: The assessment of OHL and its related factors among medical interns in Saudi Arabia. Materials and Methods: A cross-sectional study was conducted on medical interns using the OHL- adult questionnaire (OHL-AQ) for data collection. This validated questionnaire has 17 close-ended questions listed in four sections: 1 - perception and knowledge of oral health, 2 - numeracy skills for prescriptions of antibiotic and mouthwash, 3 - communication skills, and 4 - decision-making skills regarding common oral health problems. Results and Discussion: A total of 266 medical interns participated in the study (113 male and 153 female). The mean score of OHL was 10.7 ± 4.24 (out of 17), which falls in the borderline range. About 34% of medical interns had an inadequate level of OHL. OHL was not significantly correlated with age, gender, grade point average, or parent's level of education (P > 0.05). Conclusion: The present study shows that medical interns demonstrated a borderline level of OHL. Enhancement of oral health knowledge of those future physicians is recommended by the inclusion of oral health courses in their educational curriculum.